THE ASPECTS RELATED TO THE USE AND DISPOSAL OF NAIL POLISH: THE PRELIMINARY STUDY IN THE MUNICIPALITY OF DUQUE DE CAXIAS - RJ - Thode Filho, Sérgio; Maranhão, Fabíola da Silveira; Paixão, Cintia Patrícia Santos da; Costa, Ana Paula da Silva da; Almeida, Thuanny Moraes de; Talhas, Isadora Bastos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Brazil is the second largest consumer of nail polish in the world. Behind only the U.S.A. In Brazil, in 2012 this market was worth about $575.64 million, up 12.6% compared to 2011. The number of units sold in Brazil in the same period totaled 220.5 million. This study aimed, through an exploratory research, about the discard of nail after use in commercial establishments in the municipality of Duque de Caxias, RJ. The survey was conducted in the central region of Duque de Caxias and data collection instrument was a structured questionnaire. Were made 50 interviews with representatives of commercial establishments. The estimated confidence interval was 95% and the highest estimated margin of error is 10 percentage points more or less on the results for each sample. Regarding the results, it was found that all respondents commercial establishments discard the material post-consumer waste in common. When asked about the possibility of recycling, 74% are unaware of this information. We also observed the accumulation of recyclable material in landfills and urban centers, due to lack of selective collection for this residue or even specific for later reprocessing this material collection points.